Prevalent work related values among faculty members at Al Husn University College from students' point of view in Jordan (Damascus University Journal of educational and Psychologyical sciences, 2021)
The objective of the study was to investigate work related  prevalent values among faculty members at Al Husn University College Jordan from students' points of view. The  Sample of the study consisted of  439 students (283 BA, 156 diploma) selected randomly from Al Husen University College. To achieve the objective of the study, a 35 items questionnaire distributing on 6 values was developed. Validity and reliability were obtained for the questionnaire. Results indicated that the prevalent values among faculty members were as follows: honesty, consultation, fidelity, role model, human relations, and justice, respectively. No significant gender differences at (?=0.05) were found. Significant differences at (?=0.05) were found due to the  educational level, in favor of BA students. The recommended the need for more attention to promoting human relations and justice values among faculty members through organizing semi nars, lectures, workshops and meetings; as these  values have a direct effect on the interactions between students and faculty members, promote trust among them and have positive effects on teaching learning process in general.
Keywords: : Prevalent work related values faculty members; AlHusn University College Students; Jordan